Pengaruh Nilai Sosial dan Motivasi Moral terhadap Perilaku Produsen Berbasis Altruisme - Utami, Novariani Indri; Mintasih, Mintasih; Leny, Leny (Comit: Communication, Information and Technology Journal, 2025)
This study aims to examine the influence of social values and moral motivation on producer behavior based on altruism. In the conventional microeconomic framework, producers are often assumed to be rational agents who are solely profit-oriented. However, in practice, especially in the cooperative, MSME, and social entrepreneurship sectors, producer behavior shows the influence of social values and moral considerations. Social values are understood as collective norms that encourage prosocial actions, while moral motivation is an individual's internal drive to act fairly and ethically. Through a literature review and case studies in Indonesia, this paper shows that both factors contribute to the formation of production behavior that not only pursues economic efficiency, but also pays attention to social impacts and sustainability. These findings are important for broadening perspectives in economic studies and encouraging an approach to economic education that integrates ethical and social aspects.